2011
DOI: 10.1186/1297-9716-42-66
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the acute phase responses of Serum Amyloid A, Haptoglobin and Type 1 Interferon in cattle experimentally infected with foot-and-mouth disease virus serotype O

Abstract: A series of challenge experiments were performed in order to investigate the acute phase responses to foot-and-mouth disease virus (FMDV) infection in cattle and possible implications for the development of persistently infected "carriers". The host response to infection was investigated through measurements of the concentrations of the acute phase proteins (APPs) serum amyloid A (SAA) and haptoglobin (HP), as well as the bioactivity of type 1 interferon (IFN) in serum of infected animals. Results were based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
69
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(81 citation statements)
references
References 46 publications
10
69
1
1
Order By: Relevance
“…In the studies conducted, it was revealed that Saa and hp values were extremely important markers (HORADAGODA et al, 1999) in distinctive diagnosis of bacterial (AYTEKIN et al, 2016;ECKERSALL et al, 2006;GANHEIM et al, 2003;SKINNER and rOBertS, 1991;WaLker et al, 1994) and viral (BASBUG et al, 2016;GANHEIM et al, 2003;HEEGARD et al, 2000;HOFNER et al, 1994;STENFELDT et al, 2011;ULUTAS et al, 2011) diseases, and plasma levels in these diseases increased significantly.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In the studies conducted, it was revealed that Saa and hp values were extremely important markers (HORADAGODA et al, 1999) in distinctive diagnosis of bacterial (AYTEKIN et al, 2016;ECKERSALL et al, 2006;GANHEIM et al, 2003;SKINNER and rOBertS, 1991;WaLker et al, 1994) and viral (BASBUG et al, 2016;GANHEIM et al, 2003;HEEGARD et al, 2000;HOFNER et al, 1994;STENFELDT et al, 2011;ULUTAS et al, 2011) diseases, and plasma levels in these diseases increased significantly.…”
Section: Discussionmentioning
confidence: 99%
“…STENFELDT et al (2011) stated that Saa and hp increases may be used as a marker of acute infection in cattle with foot-and-mouth disease. In bovine respiratory syncytial virus caused experimentally by HEEGARD et al (2000), it was indicated that hp levels increased with the severity of the disease, Saa was the acute phase protein responding more rapidly to the infection, having higher sensitivity than hp.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations